Geospatial technologies for all : selected papers of the 21st AGILE Conference on Geographic Information Science /: selected papers of the 21st AGILE Conference on Geographic Information Science. ([2018]) - Association of Geographic Information Laboratories in Europe., Conference, (21st) 2018 (Lund, Sweden)
No abstract available